Sonic Modernities in the Malay World : A History of Popular Music, Social Distinction and Novel Lifestyles (1930s - 2000s) - Barendregt, B. (Southeast Asia Mediated, 2014)
Sonic Modernities analyses the interplay between the production of popular music, shifting ideas of the modern and, in its aftermath, processes of social differentiation in twentieth-century Southeast Asia.